Exploring how youth experience and perceive peer social support at a holistic youth development programme in the Western Cape: the Chrysalis academy - Winsted, Ellyn (Department of Social Development, 2022)
In this study, the main goal was to explore youth experiences and perceptions of peer social support in the Western Cape region of South Africa at the Chrysalis Academy youth programme. The youth in the Western Cape face many obstacles to their development such as gangsterism, drugs, unemployment, lack of social support, volatile living environments and insufficient positive youth development programmes. It was assumed in this study that positive peer social support aligns with the ‘stress-buffer' model which claims social support as a buffer to these types of stressful live events and situations. This study sought to magnify the phenomena of peer social support versus the more researched phenomena of parental and teacher support. Research has emphasised parental and teacher support as playing more important roles of social support buffers for youth. The other goal of this study was to explore the ways in which this social support helps to foster resiliency and positive youth development. This study aimed to add to existing research on youth development by providing personal experiences youth had with peers; a facet of social support the researcher assumed was overlooked and was lacking overall in the context of South Africa. This would aid in creating a more in depth understanding of the role of peer support in youth development and help to create programmes and policies that utilise peer support as a main pillar in development to foster resiliency for youth. To this end, semi-structured qualitative interviews were conducted with twenty participants who lived in different communities throughout Cape Town and the surrounding areas. The participants were graduates of the youth development programme at the Chrysalis Academy; a programme that integrates peer support into their development framework.